2020
DOI: 10.1146/annurev-biochem-010611-112801
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of P-Type ATPase Ion Pumps

Abstract: P-type ATPases are found in all kingdoms of life and constitute a wide range of cation transporters, primarily for H+, Na+, K+, Ca2+, and transition metal ions such as Cu(I), Zn(II), and Cd(II). They have been studied through a wide range of techniques, and research has gained very significant insight on their transport mechanism and regulation. Here, we review the structure, function, and dynamics of P2-ATPases including Ca2+-ATPases and Na,K-ATPase. We highlight mechanisms of functional transitions that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 126 publications
3
116
0
Order By: Relevance
“…P-type ATPases share a similar molecular architecture, which comprises three distinct cytosolic domains, i.e., the actuator (A), nucleotide binding (N) and phosphorylation (P) domains, and two transmembrane domains, the transport domain of six helical segments (TM1 to TM6), which contains the ion binding sites located halfway through the membrane, and a class-specific support domain of four helical segments (TM7 to TM10). Moreover, in many P-type ATPases, the N- or C-terminal extensions at the cytosolic side act as regulatory (R) domains, which are autoinhibitory or can function as sensors for the transported cations [ 3 , 4 ]. Interestingly, the R domains of P-type ATPases have the characteristics of disordered proteins and are therefore highly variable and flexible.…”
Section: Introductionmentioning
confidence: 99%
“…P-type ATPases share a similar molecular architecture, which comprises three distinct cytosolic domains, i.e., the actuator (A), nucleotide binding (N) and phosphorylation (P) domains, and two transmembrane domains, the transport domain of six helical segments (TM1 to TM6), which contains the ion binding sites located halfway through the membrane, and a class-specific support domain of four helical segments (TM7 to TM10). Moreover, in many P-type ATPases, the N- or C-terminal extensions at the cytosolic side act as regulatory (R) domains, which are autoinhibitory or can function as sensors for the transported cations [ 3 , 4 ]. Interestingly, the R domains of P-type ATPases have the characteristics of disordered proteins and are therefore highly variable and flexible.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ pumping maintains SR Ca 2+ stores and is performed by the sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA). SERCA transports Ca 2+ -ions against a steep electrochemical gradient by cycling through a series of conformational states with alternating access to two Ca 2+ -binding sites in the transmembrane domain 1,2 . The ATP powered reaction cycle includes the formation and breakdown of a phosphoenzyme intermediate which is characteristic of the P-type ATPase family.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and dynamics of SERCA have been described in great detail, 1,[16][17][18][19] but much less is known about HRC. Sequence analysis does not reveal any conserved domains in HRC.…”
Section: Introductionmentioning
confidence: 99%
“…S10, Supporting information), showed that binding of Ca 2+ to the transmembrane transport sites ( Fig. 1) decreases the amplitude of motion in the ion transport domain [29,30], namely in transmembrane helices M1, M3 and M4, as evidenced by a decrease in RMSF for this region (Fig. 1).…”
mentioning
confidence: 96%